Firm Characteristics, Corporate Restructuring and Performance in Malaysia - Alias, Norazlan (2008)
This study examined the relationship between specific characteristics of the firm such as board of directors' ownership, institutional ownership, concentrated ownership, debt ratio and levels of diversification which had been identified in the literature as the determinants of corporate restructuring and corporate performance before and after restructuring. Ninety three debt restructuring firms and ninety six asset restructuring firms listed on the Bursa Malaysia (formerly known as Kuala Lumpur Stock Exchanges) between 1990 and 2002 firms were selected as the final samples. The findings of the study showed that the presence of board of directors in the ownership of the firm prior to debt restructuring and asset restructuring did not support the argument that when board of directors become owners, the ownership would lead to improved performance of the firm in terms of return on total assets (ROA) and return on operating cash flow (RCF). Also, prior to debt restructuring, institutional ownership and concentrated ownership had negative relationship o n performance. However, prior to asset restructuring, institutional ownership had significant positive relationship while concentrated ownership had negative relationship on performance. The findings also revealed that the ownership structure had no significant relationship with firm's performance following debt restructuring but had significant relationship with performance fol lowing asset restructuring. In conclusion, in Malaysia, the firm's ownership structure played a role in determining performance only following asset restructuring but not debt restructuring.